Plea Bargaining dalam Sistem Peradilan Pidana Indonesia: Peluang Efisiensi atau Ancaman terhadap Hak Asasi Terdakwa - Mazayaka Atina Maryam (Jurnal Hukum Lex Generalis, 2026)
The application of plea bargaining in the Indonesian criminal justice system emerged in response to the backlog of cases following the enactment of the new Criminal Procedure Code (KUHAP). This normative legal study found that de jure, the guilty plea mechanism has been selectively regulated through Articles 78, 205 and 234 of Law Number 20 of 2025; however, de facto, inconsistent norms and the unequal position of defendants have the potential to threaten human rights. It concluded that judicial efficiency needs to be balanced with strong judicial oversight. As an operational recommendation, the Supreme Court should issue standard technical guidelines for examining voluntary guilty pleas that apply uniformly across all courts.